Language, literature, education and community: the Bengali muslim woman in the early twentieth century - Azim, Firdous; Hasan, Perween (© 2014 Elsevier Ltd., 2016)
This article was published in the Women's Studies International Forum [© 2013 Elsevier Ltd.] and the definite version is available at:http://dx.doi.org/10.1016/j.wsif.2013.10.013 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0277539513001891